2023
DOI: 10.1249/mss.0000000000003109
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Up Prolonged Sitting to Improve Cardiometabolic Risk: Dose–Response Analysis of a Randomized Crossover Trial

Abstract: PurposeSedentary time is ubiquitous in developed nations and is associated with deleterious health outcomes. Physical activity guidelines recommend reductions in sedentary time; however, quantitative guidelines that inform how often and how long sedentary time should be interrupted have not been provided. The purpose of this study was to examine the acute effects of multiple doses of a sedentary break intervention on cardiometabolic risk factors, concurrently evaluating efficacy of varying frequencies and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…Previous cross-sectional and longitudinal studies have identified interruptions or breaks in sedentary time in accelerometer data and investigated the relationships with health outcomes. [8][9][10][11] In comparison, to our knowledge this is the first workplace-based intervention study that has specifically attempted to define an interruption/activity break in a manner that more closely represents those used in laboratory studies that have shown significant health effects [17][18][19][20][21] and evaluate changes in this pattern of activity. We predefined that an OTM would be identified if the accelerometer data indicated that participants were not sitting (activPAL) and the ActiGraph data showed that counts per minutes had increased to greater than 1000 cpm, that was sustained for more than 1 minute and was preceded by ≥15 minutes of sedentary time (<150 cpm).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous cross-sectional and longitudinal studies have identified interruptions or breaks in sedentary time in accelerometer data and investigated the relationships with health outcomes. [8][9][10][11] In comparison, to our knowledge this is the first workplace-based intervention study that has specifically attempted to define an interruption/activity break in a manner that more closely represents those used in laboratory studies that have shown significant health effects [17][18][19][20][21] and evaluate changes in this pattern of activity. We predefined that an OTM would be identified if the accelerometer data indicated that participants were not sitting (activPAL) and the ActiGraph data showed that counts per minutes had increased to greater than 1000 cpm, that was sustained for more than 1 minute and was preceded by ≥15 minutes of sedentary time (<150 cpm).…”
Section: Discussionmentioning
confidence: 99%
“…Carter et al 34 prompted people to move every 45 minutes, and their qualitative data suggested that people just disliked the computer prompt and lack of activity choices in the intervention, rather than the time frame for the prompt being an issue. A recent study comparing different sedentary break frequency/duration combinations of light-intensity walking found that greatest improvements in postprandial glucose and systolic blood pressure were achieved from moving for 5 minutes after every 30 minutes of sitting, with an interruption every 60 minutes for one also resulting in similar reductions in systolic blood pressure 21 . Duran et al 21 concluded that higher-frequency, longer-duration doses of light activity are necessary to target glycemic responses and should be used in future interventions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations